The departed - Pitt, Brad; Grey, Brad; King, Graham; Scorsese, Martin; Monahan, William; Warner Bros. Pictures (Burbank, CA : Warner Home Video, 2006)
Rookie cop Billy Costigan infiltrates the mob to help bring boss Frank Costello down, but Costello has a mole of his own winning everyone's trust within the police department
Title from title screen
In English and Thai language and subtitles in English, Korean, Thai and Indonesian
Director of photography, Michael Ballhaus ; editor, Thelma Schoonmaker ; music, Howard Shore ; costume designer, Sandy Powell ; production designer, Kristi Zea ; visual effects supervisor, Rob Legato
Cast: Leonardo DiCaprio, Matt Damon, Jack Nicholson, Mark Wahlberg, Martin Sheen
Keywords: Undercover operations -- Drama; Moles (Spies) -- Drama; Organized crime -- Drama; Mafia -- Drama; Crime -- Drama